2019
DOI: 10.1159/000503914
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Telecytology in the Primary Diagnosis of Thyroid Fine-Needle Aspiration Specimens

Abstract: Introduction: The Acibadem Health Group (AHG) has been using telepathology/digital pathology stations since 2006. In 2013, the system was changed from videoconferencing to digital pathology (whole-slide imaging) utilizing 3DHISTECH scanners and software. In 2017, digital cytology started to be used for routine cytopathologic diagnosis for thyroid fine-needle aspiration (FNA) cases. Material and Methods: Two hundred and twenty-seven thyroid cases were received for analysis using telecytology (TC) during the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 10 publications
(15 reference statements)
0
12
0
1
Order By: Relevance
“…Multiple studies around the world has demonstrated beneficial effect of this strategy in decreasing the rate of inadequate specimen with US-FNA at multiple sites, including thyroid [7,[9][10][11][12]. Some even suggested using tele-cytopathology to overcome the shortage of onsite cytopathologist at some sites [13]. However, this comes with the price of prolonging the procedure time and increasing the cost, with some studies suggesting no overall benefit [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies around the world has demonstrated beneficial effect of this strategy in decreasing the rate of inadequate specimen with US-FNA at multiple sites, including thyroid [7,[9][10][11][12]. Some even suggested using tele-cytopathology to overcome the shortage of onsite cytopathologist at some sites [13]. However, this comes with the price of prolonging the procedure time and increasing the cost, with some studies suggesting no overall benefit [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…1) Cytology slides: In most cases with cell smears, liquid-based cytology, or blood smears, the results are similar to those from microscopic diagnoses made using glass slides with appropriate focus stacking (Z-stacking) during scanning and sufficient validation [52]. However, the optimal focus stacking method must be carefully selected for certain sample types (e.g., samples with many 3-dimensional structures, such as thyroid gland fine-needle aspirates [53]), staining conditions, and smear conditions. Excessive focus stacking and the acquisition of higher-magnification images (60 × 100 × or higher) could lead to over-scaling of the WSI files, which could negatively affect the operation of the entire system [6].…”
Section: Scope Of Applicationmentioning
confidence: 95%
“…When diagnoses are made using portable terminals such as a tablet PC, the use of a relatively small screen is a major concern. The results of a recent study suggest that diagnosis using portable terminals should be limited to special cases that require relatively low accuracy but rapid reporting of results, such as frozen section tests [1,53,65]. These terminals are generally not reliable for routine diagnostic work.…”
Section: Issues Related To Telepathology Firewalls Protection Of Pementioning
confidence: 99%
“…Although partly attributed to patient selection, the absence of in‐person intradepartmental consensus meetings can partially explain these results. As previously reported, there is a tendency to have a lower threshold for applying indeterminate diagnostic categories when using virtual platforms for diagnosis 10 . However, virtual platforms have enjoyed a boost during the pandemic, not only for diagnosis but also for educational purposes, allowing residents’ training to continue 5 .…”
mentioning
confidence: 94%